Pengaruh Kondisi Fasilitas dan Pengaruh Sosial Terhadap Konstruk Technology Acceptance Model pada Mahasiswa Konsumen GoPay dan OVO di Jakarta - Alfa Gratia Pelupessy; Yanuar Yanuar (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The research conducted aims to examine the effect of facility conditions and social influences on the technology acceptance model (TAM) construct consisting of perceived usefulness, perceived ease of use, attitude toward using, behavioral intentions to use, and actual use to GoPay and OVO consumers. This research was conducted on students who are actively studying at Tarumanagara University, Trisakti University, and Atmajaya University who are also GoPay and OVO users in April 2019. The sampling technique used is based on the Slovin formula. Source of research data is the result of the distribution of questionnaire instruments, where the assessment of the response of each sample is measured using a Likert scale. The results of data collection are then analyzed using the structural equation model. The results of the study prove that the condition of the facility and social influence as an external variable in the TAM model under study has a positive effect on perceived ease and perceived benefits. The results of this study explain that the better the facilities, which include facilities and infrastructure in the use of GoPay and OVO as e-money, as well as the more people who use GoPay and OVO will tend to have an impact on the formation of perceptions of convenience and perceptions of benefits that are increasingly positive so as to encourage individuals to have a positive attitude and greater interest to use GoPay and OVO to help with the activities or activities undertaken.